Laptop cooling numerical simulation using Computational Fluid Dynamics - Syamsuri Syamsuri; ZA Fairuz; KDT Alfonsus (Universitas Muhammadiyah Metro, 2020)
Laptop’s cooling solution is very important. In some cases, due to poor cooling an over heat on the mother board, main chip, and other components occurs, so that the laptop is quickly broken. Therefore it is necessary to know the temperature distribution so that over heat can be overcome. One of the methods to determine the temperature distribution in this final project is a flow simulation, using CFD (Computational Fluid Dynamics), 3D method with the variation if different air flow velocity, i.e. 5 m/s, 10 m/s, and 15 m/s. The higher the air flow rate, the higher the cooling occurs. From the temperature contours it is shown that the hot temperature is built up on the back of the heat sink. The results of the validation of this study and previous studies obtained an error that occurred was around 4%.Keywords: CFD, variation of air flow velocity, laptop.